Penggunaan Gaya Bahasa Sindiran dengan Topik Politik pada Podcast #Closethedoor dalam Konten Kanal Youtube Deddy Corbuzier - Anggi Fransiska; Alifiah Nurachmana; Paul Diman; Albertus Purwaka; Yulina Mingvianita (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
The purpose of the study is to describe: (1) the types of satirical language styles contained in the content of Deddy Corbuzier's YouTube channel, (2) the functions of satire language styles contained in the content of Deddy Corbuzier's YouTube channel, (3) the implications for learning anecdotal texts at SMK Negeri 3 Palangka Raya. This research is a qualitative descriptive research. The source of data in this study is six podcast shows #CLOSETHEDOOR with political themes owned by Deddy Corbuzier. The data in it is in the form of sentences in podcasts that use satirical language styles. The data collection technique in this study used the analysis technique of the free listening method (SBLC). The results of this study show the satirical language found in the podcast #CLOSETHEDOOR in the content of Deddy Corbuzier's YouTube channel with political themes. (1) The types of satirical language styles on Deddy Corbuzier's six #CLOSETHEDOOR podcast shows are satirical language styles of irony, cynicism and sarcasm. Satirical language style of irony satire serves to insinuate subtly without hurting the feelings of others with what is conveyed by the speaker, cynical language style of language used to insinuate with rather crude satire contains ridicule, sarcasm language style of language that contains crude insinuation to denounce someone. The satirical language style is presented by inserting a message of sensitivity in interpreting each series of speech. Of the three types of satirical language style, the most dominant is irony satire language style, the results showed that the irony satire language style, While the language style of satire, cynicism and sarcasm respectively (20 data). (2) Personal language style functions convey their speech with disappointment, anger, pleasure, etc. to the interlocutor, the referential function is to talk about the surrounding environment, interpersonal functions influence in the social context. Of the three types of language functions, the most dominant is the function of personal language style, the results showed that the function of personal language used existed (16 data), while the function of referential and interpersonal style respectively (15 data). (3) Research is implicated in learning anecdotal texts in SMK class X odd semesters, using teaching materials in the form of modules and using Phase E learning outcomes, with learning objectives contained in the discussion D. Compiling Anecdotal Text Based on Observation Exposition Text.